Modeling transitions in the California light-duty vehicles sector to achieve deep reductions in transportation greenhouse gas emissions - Leighty, Wayne; Ogden, Joan M.; Yang, Christopher (Energy policy, 2012)
California’s target for reducing economy-wide greenhouse gas (GHG) emissions is 80% below 1990 levels by 2050. We develop transition scenarios for meeting this goal in California’s transportation sector, with focus on light-duty vehicles (LDVs). We explore four questions: (1) what options are available to reduce transportation sector GHG emissions 80% below 1990 levels by 2050; (2) how rapidly would transitions in LDV markets, fuels, and travel behaviors need to occur over the next 40 years; (3) how do intermediate policy goals relate to different transition pathways; (4) how would rates of technological change and market adoption between 2010 and 2050 impact cumulative GHG emissions? We develop four LDV transition scenarios to meet the 80in50 target through a combination of travel demand reduction, fuel economy improvements, and low-carbon fuel supply, subject to restrictions on trajectories of technological change, potential market adoption of new vehicles and fuels, and resource availability. These scenarios exhibit several common themes: electrification of LDVs, rapid improvements in vehicle efficiency, and future fuels with less than half the carbon intensity of current gasoline and diesel. Availability of low-carbon biofuels and the level of travel demand reduction are “swing factors” that influence the degree of LDV electrification required. ► We model change in California LDVs for deep reduction in transportation GHG emissions. ► Reduced travel demand, improved fuel economy, and low-carbon fuels are all needed. ► Transitions must begin soon and occur quickly in order to achieve the 80in50 goal. ► Low-C biofuel supply and travel demand influence the need for rapid LDV electrification. ► Cumulative GHG emissions from LDVs can differ between strategies by up to 40%.